Kinerja Pelayanan Prima Di Kesatuan Polisi Resor Minahasa - Sarendeng, Jek Albert San; Lumolo, Johny; Kimbal, Marthen L (JURNAL ILMIAH SOCIETY, 2016)
Indonesian National Police is a state apparatus whose role of maintaining security and public order, enforcing the law, and to provide protection, shelter, and services to the community in order to maintaining security in the country. Members of the Police of the Republic of Indonesia is a civil servant at the Indonesian National Police. In service proactively, transparently, accountable to the law-abiding by the rules, procedures, ethics and governance so that it can be expected to increase public trust and internal solidity of the Indonesian National Police. This study was to examine how the performance of the police in the resort Minahasa in providing excellent service to the community, this study used a qualitative approach to unravel the phenomenon behind the service system at the level of the police station to investigate the activities System Police Services Integrated conducted by elements operational policing to the community.